PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) BERBANTU MEDIA PEMBELAJARAN PERMAINAN TRADISIONAL CUBLAK CUBLAK SUWENG KELAS V SD NEGERI 005 SAMARINDA SEBERANG - Abel, Abel; Muhlis; Diana Septika, Hety; Sukriadi; Sainal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low learning outcomes of fifth-grade students at SD Negeri 005 Samarinda Seberang, particularly in Mathematics. The research problem addressed in this study is how to improve students’ learning outcomes in Mathematics by using the Cooperative Learning Model of the Team Games Tournament (TGT) type assisted by the traditional game Cublak-Cublak Suweng as a learning medium in the fifth grade of SD Negeri 005 Samarinda Seberang. The purpose of this study is to determine how students’ Mathematics learning outcomes can be improved through the Cooperative Learning Model of the Team Games Tournament (TGT) type assisted by the traditional game Cublak-Cublak Suweng as a learning medium. This research is a Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of two meetings. The research procedure consists of four stages: planning, implementation, observation, and reflection. The subjects of this study were 25 fifth-grade students of SD Negeri 005 Samarinda Seberang, while the object of the study was to examine Mathematics learning outcomes and improvements in each cycle using the Cooperative Learning Model of the Team Games Tournament (TGT) type. Data collection techniques included observation, tests, and documentation. Data analysis techniques used averages, percentages, and graphs. The results of the study show that the average learning outcome in the initial data was 51.2, with 40% of students achieving mastery. In Cycle I, the average score increased to 61.80, with an improvement percentage of 20.70% and 64% of students achieving mastery. In Cycle II, the average score increased to 72, with an overall improvement of 41.18% from the initial data and 84% of students achieving mastery. Based on these findings, it can be concluded that Mathematics learning outcomes improved through the Cooperative Learning Model of the Team Games Tournament (TGT) type assisted by the traditional game Cublak-Cublak Suweng as a learning medium in the fifth grade of SD Negeri 005 Samarinda Seberang.